Exploring the mechanisms of host-specificity of a hyperparasitic bacterium (Pasteuria spp.) with potential to control tropical root-knot nematodes (Meloidogyne spp.): insights from Caenorhabditis elegans - Davies, Keith G.; Mohan, Sharad; Phani, Victor; Srivastava, Arohi (Frontiers in Cellular and Infection Microbiology, 2023)
Plant-parasitic nematodes are important economic pests of a range of tropical crops. Strategies for managing these pests have relied on a range of approaches, including crop rotation, the utilization of genetic resistance, cultural techniques, and since the 1950’s the use of nematicides. Although nematicides have been hugely successful in controlling nematodes, their toxicity to humans, domestic animals, beneficial organisms, and the environment has raised concerns regarding their use. Alternatives are therefore being sought. The Pasteuria group of bacteria that form endospores has generated much interest among companies wanting to develop microbial biocontrol products. A major challenge in developing these bacteria as biocontrol agents is their host-specificity; one population of the bacterium can attach to and infect one population of plant-parasitic nematode but not another of the same species. Here we will review the mechanism by which infection is initiated with the adhesion of endospores to the nematode cuticle. To understand the genetics of the molecular processes between Pasteuria endospores and the nematode cuticle, the review focuses on the nature of the bacterial adhesins and how they interact with the nematode cuticle receptors by exploiting new insights gained from studies of bacterial infections of Carnorhabditis elegans. A new Velcro-like multiple adhesin model is proposed in which the cuticle surface coat, which has an important role in endospore adhesion, is a complex extracellular matrix containing glycans originating in seam cells. The genes associated with these seam cells appear to have a dual role by retaining some characteristics of stem cells.